The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s2176-94512012000200017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of snoring and sleep apnea syndrome with a removable mandibular advancement device in patients without TMD

Abstract: Introduction: Among the sleep disorders reported by the American Academy of Sleep, the most common is obstructive sleep apnea-hypopnea syndrome (OSAHS), which is caused by difficulties in air passage and complete interruption of air flow in the airway. This syndrome is associated with increased morbidity and mortality in apneic individuals.Objective: It was the objective of this paper to evaluate a removable mandibular advancement device as it provides a noninvasive, straightforward treatment readily accepted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Similar results were obtained by Giannasi et al, 29,30 who also noted that adjustable MADs gave a greater reduction in daytime sleepiness and in snoring than the rigid appliances. Duarte et al 31 also observed the effectiveness of treating patients with adjustable MADs. In this case the device was inserted at a maximum protrusion of 60%, applying 0.5-to 1-mm increments every 2 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…Similar results were obtained by Giannasi et al, 29,30 who also noted that adjustable MADs gave a greater reduction in daytime sleepiness and in snoring than the rigid appliances. Duarte et al 31 also observed the effectiveness of treating patients with adjustable MADs. In this case the device was inserted at a maximum protrusion of 60%, applying 0.5-to 1-mm increments every 2 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…After a full‐text review, 42 studies with 2265 patients of OA were included for Meta‐analysis. The included studies included 6 TRD, 14‐19 and 35 MAD 20‐54 literature. In addition, Barthlen et al 55 incorporated both TRD and MAD.…”
Section: Resultsmentioning
confidence: 99%